2009
DOI: 10.1177/039156030907600305
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction Study on Human Male Reproductive Tract and Semen

Abstract: In the present study authors had separated testis, epididymis-caput, corpus, cauda, vas deferens, seminal vesicle, prostate gland and bulbourethral gland from human male reproductive tract, made it to ash form. Semen also underwent same procedure. All samples had undergone X-ray diffraction analysis. Results Results showed there where two distinct rings for each sample. We named it is “A” &” B”. Under “A” Barium silicate, Barium silicate hydrate and three metal complexes of copper, gold and zinc were seen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…This is the first of its kind to report presence of gold inside sperm cell. The result of the present study supported earlier reports of gold in human semen and in male genital system [3][4][5][6]. Gold was seen in epididymis caput (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is the first of its kind to report presence of gold inside sperm cell. The result of the present study supported earlier reports of gold in human semen and in male genital system [3][4][5][6]. Gold was seen in epididymis caput (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The gold in sperm cells might have entered during spermatogenesis. X-ray diffraction analysis showed gold as present in testes [5]. In an unpublished histological study, we observed gold particles in the rim of seminiferous tubule of frog (Sumangala, Skandhan).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Histologically, gold was seen in the rim of seminiferous tubules of frog (personal communication, Sumangala, Skandhan). X-ray diffraction study has shown gold in trimetal form in male system throughout the length of it [50]. Possibly yellow metal is released to semen from throughout the length of germinal system.…”
Section: Discussionmentioning
confidence: 99%